Polyethylene glycol‐fusion repair of sciatic allografts in female rats achieves immunotolerance via attenuated innate and adaptive responses. Issue 12 (15th September 2020) - Smith, Tyler A.; Ghergherehchi, Cameron L.; Mikesh, Michelle; Shores, Jaimie T.; Tucker, Haley O.; Bittner, George D.
Abstract: Ablation/segmental loss peripheral nerve injuries (PNIs) exhibit poor functional recovery due to slow and inaccurate outgrowth of regenerating axons. Viable peripheral nerve allografts (PNAs) as growth‐guide conduits are immunologically rejected and all anucleated donor/host axonal segments undergo Wallerian degeneration. In contrast, we report that ablation‐type sciatic PNIs repaired by neurorrhaphy of viable sciatic PNAs and a polyethylene glycol (PEG)‐fusion protocol using PEG immediately restored axonal continuity for many axons, reinnervated/maintained their neuromuscular junctions, and prevented much Wallerian degeneration. PEG‐fused PNAs permanently restored many sciatic‐mediated behaviors within 2–6 weeks. PEG‐fused PNAs were not rejected even though host/donors were neither immunosuppressed nor tissue‐matched in outbred female Sprague Dawley rats. Innate and adaptive immune responses to PEG‐fused sciatic PNAs were analyzed using electron microscopy, immunohistochemistry, and quantitative reverse transcription polymerase chain reaction for morphological features, T cell and macrophage infiltration, major histocompatibility complex (MHC) expression, apoptosis, expression of cytokines, chemokines, and cytotoxic effectors. PEG‐fused PNAs exhibited attenuated innate and adaptive immune responses by 14–21 days postoperatively, as evidenced by (a) many axons and cells remaining viable, (b) significantly reduced infiltration of cytotoxic and total T cells and macrophages, (c) significantly reduced expression of inflammatory cytokines, chemokines, and MHC proteins, (d) consistently low apoptotic response. Morphologically and/or biochemically, PEG‐fused sciatic PNAs often resembled sciatic autografts or intact sciatic nerves. In brief, PEG‐fused PNAs are an unstudied, perhaps unique, example of immune tolerance of viable allograft tissue in a nonimmune‐privileged environment and could greatly improve the clinical outcomes for PNIs relative to current protocols. Abstract : Innate and adaptive immune responses to sciatic nerve allografts treated with a polyethylene glycol (PEG)‐fusion repair protocol were compared to those in negative control allografts untreated by PEG. By 21 days PO, PEG‐fused allografts showed significantly reduced major histocompatibility complex class I expression and T cell (CD3) infiltration. PEG‐fused allografts more closely resembled unoperated nerves.